An improved model on forecasting temperature rise of high-speed angular contact ball bearings considering structural constraints. Issue 1 (8th January 2018) - Zheng, De-xing; Chen, Weifang; Li, Miaomiao
Abstract : Purpose: Thermal performances are key factors impacting the operation of angular contact ball bearings. Heat generation and transfer about angular contact ball bearings, however, have not been addressed thoroughly. So far, most researchers only considered the convection effect between bearing housings and air, whereas the cooling/lubrication operation parameters and configuration effect were not taken into account when analyzing the thermal behaviors of bearings. This paper aims to analyze the structural constraints of high-speed spindle, structural features of bearing, heat conduction and convection to study the heat generation and transfer of high-speed angular contact ball bearings. Design/methodology/approach: Based on the generalized Ohm's law, the thermal grid model of angular contact ball bearing of high-speed spindle was first established. Next Gauss–Seidel method was used to solve the equations group by Matlab, and the nodes temperature was calculated. Finally, the bearing temperature rise was tested, and the comparative analysis was made with the simulation results. Findings: The results indicate that the simulation results of bearing temperature rise for the proposed model are in better agreement with the test values. So, the thermal grid model established is verified. Originality/value: This paper shows an improved model on forecasting temperature rise of high-speed angular contact ball bearings. In modeling, the cooling/lubrication operation parameters and structural constraints are integrated. As a result, the bearing temperature variation can be forecasted more accurately, which may be beneficial to improve bearing operating accuracy and bearing service life.